TANTANGAN DAKWAH DALAM MEDIA TEKNOLOGI KOMUNIKASI DI ERA GLOBALISASI - Rais Ribha Rifqi Hakim (Jurnal Ilmu Dakwah, 2018)
The development of information technology has kemjauan very rapidly. The advancement has led mankind easier to relate to one another. Various information and events happening parts of the world with rapidly can be known by human beings on other continents. The era of globalization characterized by the rapid advancement of communication technology is also called information age. The world community, including Muslims today can enjoy television programs with a variety of impressions. The television broadcasts emanating not only from a national network, but also can follow the international network thanks to the satellite which is connected with the parabola in people's homes. Communication on one side convey information to others for ideas or ideas to others either use or not use the media while the media on the other hand want to change the mindset and behavior of the people. Same with da'wah, Communication is the process of conveying information to others about ideas or ideas to other people both using the media and not using media while on the other hand they want to change people's mindsets and behavior. The function of da'wah and communication are also the same, namely to change someone with a specific purpose. The purpose of da'wah is to convey information and seek information to mad'u so that the material to be conveyed can be understood so that communication can be achieved. The da'i to mad’u's da'wah process is expected to have a psychological influence in improving Islamic teachings. However, the challenge of preaching in the information era has become more complex. With this required expertise in conveying his da'wah for the success of da'wah, including various treatments that are more profound and efficient. ****Perkembangan teknologi informasi mengalami kemajuan sangat pesat. Kemajuan tersebut telah mengantarkan umat manusia semakin mudah untuk berhubungan satu dengan lainnya. Berbagai infomasi dan peristiwa yang terjadi dibelahan dunia dengan secara cepat dapat diketahui oleh manusia pada benua yang lain. Era globalisasi yang ditandai oleh semakin majunya teknologi komunikasi juga disebut dengan era informasi. Masyarakat dunia termasuk umat Islam dewasa ini dapat menikmati acara televisi dengan berbagai tayangan. Siaran televisi tersebut bukan hanya terpancar dari jaringan yang bersifat nasional, tetapi juga dapat mengikuti jaringan internasional berkat adanya satelit yang dihubungkan dengan adanya parabola di rumah-rumah penduduk. Sama dengan dakwah, Komunikasi adalah proses menyampaikan informasi kepada orang lain terhadap gagasan atau ide kepada orang lain baik menggunakan media maupun tidak menggunakan media sedangkan disisi lain ingin mengubah pola pikir dan tingkah laku masyarakat. Fungsi dakwah dan komunikasi juga sama, yaitu untuk merubah seseorang dengan tujuan tertentu. Tujuan dakwah adalah untuk menyampaikan informasi dan mencari informasi kepada mad’u agar materi yang ingin disampaikan dapat dimengerti sehingga komunikasi yang dilaksanakan dapat tercapai. Proses dakwah yang dilakukan oleh da’i kepada mad’u diharapkan mempunyai pengaruh psikologis dalam meningkatkan ajaran Islam. Namun, tantangan berdakwah di era informasi menjadi lebih komplek. Dengan ini dibutuhkan kepiawaian da’i dalam menyampaikan dakwahnya demi keberhasilan dakwah, termasuk berbagai perlakuan yang lebih mendalam dan berdayaguna.